Entre permanências e mudanças: a história do ensino de História, no Colégio Estadual Clériston Andrade, da rede estadual de Eunápolis-BA (1993-1999) - Alem, Nathalia Helena (2010)
The research undertaken in this work is enrolled in the field of History of Education, in special of them disciplines pertaining to school. . It has as object the History of the education of History in a college of the state net of the Bahia, the Clériston de Andrade, between the years of 1993-1999. In the course of research seek to understand what are the main regulatory changes that have occurred for discipline in the state, as these were appropriated by teachers at schools in question and what changes have been incorporated into their teaching. We undertook this sense, a search was guided by theoretical and methodological canons of history referenced by authors linked the so-called Cultural History. We make use of passbooks, matrices, legislation, documents manuscripts for the professors and proposals, as well as, of interviews with professors and technician of the Clériston de Andrade and the Department of Education - 08, we used both for the contributions of Oral History. We realized that between the discourse of change built into regulations of statutory bodies, among which, the Curriculum Guidelines for Elementary Education History (BAHIA,1995) and the lessons of discipline that came to pass within the school, there is a distance that can be understood by the actions and strategies used in its implementation by the various constituent elements of that reality school and its characters, and the relationship with the same textbooks that the school got into the period.